Introduction to Peace Building in Post-Conflict Contexts (In Factis Pax: Journal of Peace Education and Social Justice, 2017)
This special issue is inspired by the 2016 Peace Accords in Colombia to end the fifty years’ war. Peace negotiations took place between the government and the FARC guerilla leadership. Despite this major achievement, serious concerns remain for how Colombians can actualize this accord into an authentic transition from deadly civil war to alternative, non-violent, constructive relations.
Keywords: Peace Building; Post-Conflict